Social Support and Academic Motivation of Students at Risk of Dropping Out - Emelyn Ramos; Celo I. Magallanes (Philippine Social Science Journal, 2021)
Numerous students in a high school in Negros Occidental are at risk of dropping out. However, literature linking their social support and academic motivation is scarce. This descriptive-correlational research investigated the degree of social support and academic motivation of 336 students at risk of dropping out (SARDO) using the Multidimensional Scale of Perceived Social Support and Academic Motivation Scale (AMS-HS 28) High School Version and the relationship between these variables. Demographic variables included sex, year level, family monthly income, family structure, and SARDO category. Results revealed a high degree of social support and academic motivation and a nonsignificant relationship between the demographics and the two variables. However, social support and academic motivation correlated significantly. The results served as the basis for the proposed intervention program aimed to cater to the SARDO’s needs.